Reuse of cold drink packaging based on sustainable theory. Issue 6 (January 2021) - Jun, Han; Chen, Derun
Abstract: In today's society, product packaging is increasing, and more and more kinds of materials are used, and different kinds of materials also have many difficulties in the later product recycling. Each link is closely related to the environment. From the designer's point of view, it is very important to consider the abandonment of products from the early stage of design. How to make the cold drink packaging play its residual value is to apply the sustainable theory to solve the problem.